2017
DOI: 10.1292/jvms.16-0489
|View full text |Cite
|
Sign up to set email alerts
|

Development of a one-run real-time PCR detection system for pathogens associated with bovine respiratory disease complex

Abstract: Bovine respiratory disease complex (BRDC) is frequently found in cattle worldwide. The etiology of BRDC is complicated by infections with multiple pathogens, making identification of the causal pathogen difficult. Here, we developed a detection system by applying TaqMan real-time PCR (Dembo respiratory-PCR) to screen a broad range of microbes associated with BRDC in a single run. We selected 16 bovine respiratory pathogens (bovine viral diarrhea virus, bovine coronavirus, bovine parainfluenza virus 3, bovine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
102
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 29 publications
0
102
0
Order By: Relevance
“…It is important to note that although multiplex detection may help in the diagnosis of mixed mollicute infections, it may introduce additional complexity into the determination of disease aetiology; multiple mycoplasma species may be found, for example, in the upper respiratory or genital tracts that are apparent commensals with questionable significance in disease (Brown et al., ). Another broad category of nucleic acid‐based methods is multipathogen panel PCR that allows simultaneous detection of M. bovis with other bacterial and viral pathogens from BRD (Kishimoto et al., ), milk ( bactotype Mastitis HP3 PCR Kit, Qiagen; PathoProof Mastitis Major‐3 Kit; Thermo Fisher Scientific) or aborted bovine clinical samples (Tramuta et al., ). In addition, several loop‐mediated isothermal amplification (LAMP) assays, which have potential utility as pen‐side tests for M. bovis detection, have been reported recently (Ashraf et al., ; Bai et al., ; Higa et al., ), but should undergo extensive validation to ensure reliability of results.…”
Section: The Causative Organismmentioning
confidence: 99%
“…It is important to note that although multiplex detection may help in the diagnosis of mixed mollicute infections, it may introduce additional complexity into the determination of disease aetiology; multiple mycoplasma species may be found, for example, in the upper respiratory or genital tracts that are apparent commensals with questionable significance in disease (Brown et al., ). Another broad category of nucleic acid‐based methods is multipathogen panel PCR that allows simultaneous detection of M. bovis with other bacterial and viral pathogens from BRD (Kishimoto et al., ), milk ( bactotype Mastitis HP3 PCR Kit, Qiagen; PathoProof Mastitis Major‐3 Kit; Thermo Fisher Scientific) or aborted bovine clinical samples (Tramuta et al., ). In addition, several loop‐mediated isothermal amplification (LAMP) assays, which have potential utility as pen‐side tests for M. bovis detection, have been reported recently (Ashraf et al., ; Bai et al., ; Higa et al., ), but should undergo extensive validation to ensure reliability of results.…”
Section: The Causative Organismmentioning
confidence: 99%
“…Recently several multiplex real-time PCR assays have been developed to detect pathogens associated with BRDC and BED (Horwood and Mahony, 2011;Marley et al, 2008;Thonur et al, 2012;Cho et al, 2010). Alternatively, a real-time PCR based system was described that includes multiple reactions in one-run with similar thermal cycling conditions for detection of BRDC and BED pathogens (Kishimoto et al, 2017;Tsuchiaka et al, 2016). Although these real-time PCR assays are rapid and highly sensitive, their multiplexing capability at present is restricted by the availability of limited number of compatible fluorescent dyes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficiency and sensitivity of a multiplex PCR can be compromised due to primer and probe sets interfering, or the competition for the components in the reaction (Kalle et al, 2014;Parker et al, 2015). In this study, the commercially-available multiplex qPCR Pneumo4B and Pneumo4V assays demonstrated that their efficiencies for seven of these target pathogens (93-106% and 91-104%, respectively) were comparable to those of published singleplex qPCR assays (84.2-101.8%) (Kishimoto et al, 2017). Pneumo4B and Pneumo4V were able to detect between 10 copies of genomic DNA and 10-50 copies of target RNA per reaction, respectively, which are comparable to previously established methods which reported of 100-250 copies per reaction (Rahpaya et al, 2018).…”
Section: Discussionmentioning
confidence: 55%
“…While serological assays such as ELISA are frequently used to indicate prior infection with M. bovis, false negative results in early infection occur as seroconversion normally takes two weeks or more (Howard et al, 1986;Petersen et al, 2018). A wide range of polymerase chain reaction (PCR) assays have been developed to test individually for each of the pathogens involved in BRD (Amer et al, 2013;Bell et al, 2014;Klem et al, 2019;Kishimoto et al, 2017;Rahpaya et al, 2018). However, testing for multiple BRD pathogens in separate assays is prohibitively expensive for livestock producers.…”
Section: Introductionmentioning
confidence: 99%